Penerapan Media Pembelajaran Peta Interaktif Untuk Meningkatkan Pemahaman Mata Pelajaran Sejarah Kebudayaan Islam Materi Hijrah Nabi Muhammad SAW. Dari Mekkah Ke Madinah Pada Siswa Kelas IV MIS Darunnajah Cipining - Nisa, Nabila Zakiyyatun; Zakiyyatun Nisa, Nabila (Journal of Society and Scientific Studies, 2025)
Teaching Islamic Cultural History to elementary school/Madrasah Ibtidaiyah students and their equivalents presents various challenges, one of which is making the subject matter more interesting and relevant to the students' needs. This study aims to apply interactive map learning media to the subject of Islamic Cultural History for elementary school students and their equivalents. This study aims to apply interactive map learning media in Islamic Cultural History lessons for elementary school students and equivalent levels. The results of applying this interactive map learning media can serve as a simple example of the practical and methodical application of technology in learning and education, as well as a reference for other researchers who wish to develop similar products.